Effect of continental slope on N-wave type tsunami run-up. Issue 2 (August 2016) - Siva, Moode; Behera, Manasa Ranjan
Frequent tsunamis across the globe have devastated the coasts and led to significant loss of life and property. This calls for a better understanding and estimation of the tsunami characteristics. Considering the scale of the problem, numerical modelling is the most suitable method for tsunami simulation and understanding. Most tsunamis are long-period wave and governed by shallow water equations. Although tsunami is expected to initiate in the deeper waters with very less height, it may have significant amplification while traversing over the slopes. In this study, an attempt is made to understand the effect of continental slope on the transmission, propagation and run-up of tsunami. This study provides better understanding of the physical process through computation of tsunami run-up height and arrival time. To carry out this investigation and to get a preliminary understanding, a one-dimensional numerical model study is carried out using shallow water equations. These equations are solved using Crank–Nicolson finite difference approximation method on a staggered grid. This study is carried out by considering N-wave-type tsunami profile with leading depression (trough). In this study, various continental slope profiles available along the Indian coast were considered. The amplification or attenuation of the tsunami characteristics over these cross-sections was studied. Significant change in the tsunami run-up is observed for different continental slope and water depth on continental shelf.